Analysis of Factors Relate to The behavior of Preventing the Spread of COVID-19 - David Ndapa Hambur; Ribka Limbu; Enjelita M. Ndoen (Journal of Health and Behavioral Science, 2022)
Coronavirus Disease 2019 (COVID-19) is an acute respiratory infectious disease that has recently been a serious concern of the international community. Efforts to prevent COVID-19 are to apply 5M (Wearing Masks, Maintaining Distance, Washing Hands with Soap (CTPS), Staying away from Crowds, and Reducing Mobility). The purpose of this study was to analyze factors related to the behavior of preventing the transmission of COVID-19 among UMKM traders in the Oebobo Sub-District. This research is quantitative research with a cross-sectional approach involving 101 people who were taken using the cluster sampling technique. The results showed that knowledge, attitude, and people’s behavior were associated with COVID-19 prevention behavior (p-value= 0.000 consecutively). In contrast, there was no relationship between the availability of CTPS facilities and COVID-19 prevention behavior (p-value= 0.087). The government and health workers are expected to improve education and health promotion for UMKM traders in the Oebobo Sub-District about the importance of implementing health protocols to prevent COVID-19.